Archiwum klonów drzew matecznych sosny zwyczajnej (Pinus sylvestris L.) z południowo-zachodniej Litwy - Korczyk, Adolf; Myszczyńska, Izabela (Leśne Prace Badawcze, 2012)
A cohort of 366 grafts reared from 47 plus trees of Pinus sylvestris L. representing 6 distinct provenances from south-west Lithuania were planted in the clone archive in the Pomorze Forest District (in the Polish part of the Augustowska Forest). The grafts were characterized by weak growth and high mortality, in fact only 67.8% of grafts survived 10 years after planting in the archive. They will remain for use in research on the genetic variability of wild pines.